Valorization of local agro-residues for the cultivation of Pleurotus djamor (Rumph. Ex Fr.) Boedijn and their effects on nutritional value - Inci, Sule; Kirbag, Sevda; Akyuz, Mehmet (Springer Heidelberg, 2025)
Many factors, such as population growth in the world, the need for different agricultural products, the lack of sufficient agricultural products, and export potential, create a large amount of lignocellulosic waste every year as a result of agricultural harvest. Cultivating edible mushrooms, which is one of the important areas of the agricultural sector, is a simple, environmentally friendly and biological process carried out without any chemical treatment using lignocellulosic wastes. They are cultured on various local agro-residues and are an important food source with delicious, nutritious, and medicinal values. The present research aimed to evaluate some local agro-wastes for P. djamor love mushroom-pink oyster mushroom culture and determine their effects on nutritional properties. Three different compost groups were created: wheat straw (WS), quinoa stalk (QS), and their mixture in a 1:1 ratio. While no significant difference was observed in about spawn colonization days on various agro-residues (p<0.05), it was observed that the best culture medium was quinoa stalk (QS) regarding the primordia formation period (20.3 days), total harvest period (50.0 days), and yield (23.5 g/100 g). Dry P. djamor contains about 89.9-91.4% dry matter, 8.6-10.1% moisture, 250.8-277.5 kcal energy, 22.0-41.2% crude protein, 1.1-1.7% fat, 5.8-9.6% ash, 82.0-84.1% organic matter, and 20.3-38.2% nitrogen-free extract. Protein, carbohydrate, ash, and energy contents differed significantly, with the highest protein content obtained in WS-QS (1:1) (41.2%). Vitamin levels (A, E, C, and MDA) may vary, but the best compost medium for element content is QS. Ni, Cr, Co, and Cd concentrations were also detected below standards. P. djamor is an important nutrient that can be used in a balanced diet, as it contains significant amounts of protein, vitamins, and various nutritional minerals, as well as low fat and energy content. Considering all these features, this species may become a helpful food source in nutrition.
Keywords: Agro-residues; Cultured mushroom; Pleurotus djamor; Growing period; Nutritional content